PENERAPAN PROJECT-BASED LEARNING (PjBL) DALAM TEMA AKU CINTA LINGKUNGAN UNTUK MENGEMBANGKAN KARAKTER PEDULI LINGKUNGAN - Euis Siti Aisyah, - (2023)
One of the characters that can be developed in children is the character of caring for the environment which is an important element in education to shape children so they are accustomed to looking after, respecting and loving the environment. Based on data obtained by researchers, it was found that 10 out of 17 children in group B1 at the Pembina Subang State Kindergarten were found to still be throwing rubbish carelessly, children were scribbling on the walls, children were not yet able to care for plants and look after animals in the school environment. The application of learning methods presented by the teacher is also less varied, namely through habituation and storytelling. For this reason, other efforts are needed to develop environmentally caring characters in children. Project-based learning is an effective learning method because children will explore and obtain various learning outcomes in the form of attitudes, skills and knowledge about how to protect and care for the environment. This research uses a qualitative descriptive method with the Kemmis and Mc model classroom action research approach Taggart (1997). Data collection techniques include interviews, observations and documentation studies involving teachers and children at the Pembina Subang State Kindergarten. The data analysis technique is a qualitative descriptive model by Miles and Huberman (1994). The results of environmental concern research that emerged during the action were, (1) children were willing to keep the environment clean, (2) children threw rubbish in the right place, (3) children watered the plants, (4) children looked after the animals around them. It is hoped that the recommendations in this research will increase the insight, knowledge and understanding of teachers regarding the application of project- based learning in developing environmentally caring character. Keywords: Project-based learning, theme I love the environment, character who cares about the environment.